The plasticity of indium antimonide: Insights from variable temperature, strain rate jump micro-compression testing. (March 2016) - Wheeler, J.M.; Thilly, L.; Morel, A.; Taylor, A.A.; Montagne, A.; Ghisleni, R.; Michler, J.
Abstract: At ambient temperature and pressure, most of the semiconductor materials are brittle. Traditionally, use of confining pressure via indentation or a hydrostatic confining medium has been required to study the plasticity of such brittle materials below their brittle-to-ductile transition. However, previous work has demonstrated that sample miniaturization can prevent the onset of cracking and allow plastic deformation. Here, micro-compression testing has been performed at temperatures from −4 to 300 °C in situ in the SEM to measure and observe the deformation of InSb. Strain rate jump micro-compression was also used at elevated temperatures to investigate the changes in strain rate sensitivity above and below the ductile-to-brittle transition. Results indicate that the flow stress follows similar trends to those observed in bulk testing with different confining media. Observations in the deformation morphology, activation energies, and activation volumes confirms that a transition from partial to perfect dislocations occurs at the ductile-to-brittle transition temperature, i.e. around 150 °C for InSb. At very low temperature (below room temperature), first results suggest another transition in dislocation nature, as observed in bulk samples. Graphical abstract: